TIME FOR COFFEE is an essential component in the maintenance of metabolic homeostasis in Arabidopsis thaliana. (23rd August 2013) - Sanchez‐Villarreal, Alfredo; Shin, Jieun; Bujdoso, Nora; Obata, Toshihiro; Neumann, Ulla; Du, Shen‐Xiu; Ding, Zhaojun; Davis, Amanda M.; Shindo, Takayuki; Schmelzer, Elmon; Sulpice, Ronan; Nunes‐Nesi, Adriano; et al.
Summary Plants often respond to environmental changes by reprogramming metabolic and stress‐associated pathways. Homeostatic integration of signaling is a central requirement for ensuring metabolic stability in living organisms. Under diurnal conditions, properly timed rhythmic metabolism provides fitness benefits to plants. TIME FOR COFFEE (TIC) is a circadian regulator known to be involved in clock resetting at dawn. Here we explored the mechanism of influence of TIC in plant growth and development, as initiated by a microarray analysis. This global profiling showed that a loss of TIC function causes a major reprogramming of gene expression that predicts numerous developmental, metabolic, and stress‐related phenotypes. This led us to demonstrate that this mutant exhibits late flowering, a plastochron defect, and diverse anatomical phenotypes. We further observed a starch‐excess phenotype and altered soluble carbohydrate levels. tic exhibited hypersensitivity to oxidative stress and abscisic acid, and this was associated with a striking resistance to drought. These phenotypes were connected to an increase in total glutathione levels that correlated with a readjustment of amino acids and polyamine pools. By comparatively analyzing our transcriptomic and metabolomic data, we concluded that TIC is a central element in plant homeostasis that integrates and coordinates developmental, metabolic, and environmental signals.